Flexible Transparent Field‐Effect Diodes Fabricated at Low‐Temperature with All‐Oxide Materials. (8th March 2016) - Zhang, Yonghui; Mei, Zengxia; Cui, Shujuan; Liang, Huili; Liu, Yaoping; Du, Xiaolong
Abstract : Flexible fully transparent diodes with high rectification ratio of 5 × 10 8 are fabricated with all‐oxide materials at low temperature. The devices are optically transparent in the visible spectra range and electrically robust under mechanically bending. Distinguished from other diodes, these diodes utilize diode‐connected thin‐film transistor architecture and follow field‐effect principles.